E-Report Engineering System for Senior High School in Lampung - Melda Agarina; Sutedi Sutedi; Arman Suryadi Karim; Rini Nurlistiani (Proceeding International Conference on Information Technology and Business, 2022)
one of the most important parts of a school is the students and their grades. Not infrequently, the storage and reporting of student grades is recorded and stored conventionally. Therefore, it takes a long time for the process. While the results of value processing can only be seen at the end of the semester, both by students and parents of students only in the form of report cards called report cards. Therefore, the school still has difficulties in processing grades, both daily grades and final grades, although the processing has been arranged but is still not optimal. The system that was built aims to simplify the process of assessing and absenteeism students using a web-based system. The method used, namely RUP, is one of the many processes contained in the Rational Process Library, which provides the best simulation for the development or needs of the project. The system is designed with UML diagrams and is built using the PHP programming language and The Mysql database. The results of the research are mobile web-based applications built online by producing features such as data processing of teachers, students, curriculum, courses, materials, assessments, attendance and report recaps. Based on the grades processed by the teacher, they can then produce reports in the form of assessment reports based on materials and reports on overall student progress that can be accessed online by parents. Keywords— Design, Information System, E-Reporting, School.